PENDAMPINGAN HUKUM TERHADAP PERMOHONAN GANTI NAMA KARENA PINDAH AGAMA: STUDI KASUS JOANNA GRACE - Syakira Edriamarsha Firdaus; Syarifaatul Hidayah; Rimarshanda Anugrahita; Aida Dian Rami (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This writing explores the provision of legal aid assistance for individuals seeking a name change due to religious conversion, with a case study on the name change petition from Joanna Grace to Syifa Nur Cahya. It employs an empirical juridical approach, combining normative legal analysis with real-world practices observed in the field. The main focus lies in assessing the implementation and effectiveness of legal aid provided by legal aid institutions in ensuring access to justice for economically disadvantaged individuals. The findings reveal that although the assistance offered was limited in scope (non-litigation), the role of legal aid facilitators was essential in supporting administrative procedures, assisting with document preparation, and bridging communication between the client and a licensed advocate. The name change petition, classified as a voluntary legal matter, allows the court to grant a legal identity change based on valid reasons, including religious grounds. This writing highlights that legal aid functions not only as a formal legal mechanism but also as a social bridge that guarantees every citizen’s right to legal recognition and protection in accordance with their new identity